Stuck on a plateau? A model-based approach to fundamental issues in visual temporal-order judgments - Tünnermann, Jan; Scharlau, Ingrid (Vision)

Freiraum zur individuellen Reflexion gemeinsamer Werte - Geierhos, Michaela (Integration und Toleranz)

Changing Uses of the City in Contemporary Black British Novels - Tönnies, Merle; Lienen, Anna (Resistance and the City. Negotiating Urban Identities: Race, Class, Gender)

Visualising Memory Loss and the Politics of Representation in Contemporary Portraiture - Strauß, Sara (Age Matters)

Identity Politics in George Lucas’ Star Wars. by John C. McDowell - Flotmann-Scholz, Christina (Cercles: Revue Pluridisciplinaire du Monde Anglophone)

Rate Your Physician: Findings from a Lithuanian Physician Rating Website - Bäumer, Frederik Simon; Kersting, Joschka; Kuršelis, Vytautas; Geierhos, Michaela (Communications in Computer and Information Science)
Physician review websites are known around the world. Patients review the subjectively experienced quality of medical services supplied to them and publish an overall rating on the Internet, where quantitative grades and qualitative texts come together. On the one hand, these new possibilities reduce the imbalance of power between health care providers and patients, but on the other hand, they can also damage the usually very intimate relationship between health care providers and patients. Review websites must meet these requirements with a high level of responsibility and service quality. In this paper, we look at the situation in Lithuania: Especially, we are interested in the available possibilities of evaluation and interaction, and the quality of a particular review website measured against the available data. We thereby identify quality weaknesses and lay the foundation for future research.
Keywords: Lithuanian physician review websites; Medical service ratings

NLP in OTF Computing: Current Approaches and Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 24th International Conference on Information and Software Technologies (ICIST 2018))
On-The-Fly Computing is the vision of covering software needs of end users by fully-automatic compositions of existing software services. End users will receive so-called service compositions tailored to their very individual needs, based on natural language software descriptions. This everyday language may contain inaccuracies and incompleteness, which are well-known challenges in requirements engineering. In addition to existing approaches that try to automatically identify and correct these deficits, there are also new trends to involve users more in the elaboration and refinement process. In this paper, we present the relevant state of the art in the field of automated detection and compensation of multiple inaccuracies in natural language service descriptions and name open challenges needed to be tackled in NL-based software service composition.
Keywords: Inaccuracy detection; Natural language software requirements

Text Broom: A ML-based Tool to Detect and Highlight Privacy Breaches in Physician Reviews: An Insight into Our Current Work - Bäumer, Frederik Simon; Geierhos, Michaela (European Conference on Data Analysis 2018: Multidisciplinary Facets of Data Science - Book of Abstracts)

Analysing Constructional Change: Linguistic Annotation and Sources of Uncertainty - Merten, Marie-Luis; Seemann, Nina (Proceedings of the 6th International Conference on Technological Ecosystems for Enhancing Multiculturality (TEEM'18))
This paper presents the various sources of uncertainty we encounter in our project. Our research focus lies on the investigation of language elaboration processes in Middle Low German. We are particularly interested in diachronic constructional changes and constructionalizations involving and affecting all linguistic dimensions. For this, it is necessary to annotate our corpus with Part-of-Speech and constructional tags. Here, we are confronted with gradualness, gradience, and ambiguity as potential sources of uncertainty that complicate the annotation process. Furthermore, due to the historicity of the investigated language, we expect cases of incomplete knowledge and comparative fallacy from the annotators. For this reason, we develop an interface that captures all annotators’ doubts.
Keywords: historical languages; linguistic annotations; gradience and gradualness; ambiguity; incomplete knowledge

Towards a Multi-Stage Approach to Detect Privacy Breaches in Physician Reviews - Bäumer, Frederik Simon; Kersting, Joschka; Orlikowski, Matthias; Geierhos, Michaela (Proceedings of the Posters and Demos Track of the 14th International Conference on Semantic Systems co-located with the 14th International Conference on Semantic Systems (SEMANTiCS 2018))
Physician Review Websites allow users to evaluate their experiences with health services. As these evaluations are regularly contextualized with facts from users’ private lives, they often accidentally disclose personal information on the Web. This poses a serious threat to users’ privacy. In this paper, we report on early work in progress on “Text Broom”, a tool to detect privacy breaches in user-generated texts. For this purpose, we conceptualize a pipeline which combines methods of Natural Language Processing such as Named Entity Recognition, linguistic patterns and domain-specific Machine Learning approaches which have the potential to recognize privacy violations with wide coverage. A prototypical web application is openly accesible.
Keywords: Detection of Privacy Violations; Physician Reviews